Gênero Textual na Metodologia de Pesquisa em Gramaticalização - Laura Camisassa Rodrigues Lobato (2009)
The theme of this paper is the question of genre in corpora selection for diachronic linguistic investigations. The aim of this research is to demonstrate that different genres favor certain uses, and that this matter puts into question the necessity of strictness in the selectionof the texts that shall compose the corpora for diachronic studies more specifically, grammaticalization processes studies. Our suggestion is that the selected texts should belong to functionally analogous genres.Regarded only as empirical basis for the verification of the proposed theme, the grammaticalization of the modal verbs poder, dever, and querer was observed, for it is a phenomenon which can be observed from a diachronic point of view and which have already been the aim of several studies. The observation of the grammaticalization of the mentioned verbs was based on a corpus composed by four genres taken from contemporary language and by four functionally analogous genres from the XVIIIth century. During the appreciation of quantitative results, the influence of genre over the linguistic choices was observed.After this procedure, it has been noticed that, in order to obtain a truly balanced data, the control of genre, when selecting texts to build corpora for linguistic researches of this kind, is essential; and that, for a more reliable methodology, one should prefer functionally analogous samples of genres from different periods of time.